The three escapes of Hannah Arendt : a tyranny of truth - Krimstein, Ken (Bloomsbury Publishing, 2018)
Provides an illustrated biography of Hannah Arendt, one of the most prominent philosophers of the twentieth century, a hero of political thought, and a complex, controversial, deeply flawed, and courageous woman. Her intelligence and "virulent truth telling" led her to insights into the human condition, and her experience continues to shine a light on how to live as an individual and a public citizen in troubled times. --Adapted from publisher description